(untitled) (Journal of Atomic and Molecular Sciences, 2014)
We extended the aromaticity concept to all-metallic anion La^2-_4 and then performed Ab intio calculations (B3LYP/LANL2DZ, B3PW91/LANL2DZ andMP2/LANL2DZ) on the selected structures. The computed results indicate that anion La^2-_4 has two stable isomers: one is the bidentate C_2v structure and another is the square planar D_4h structure. The further analysis on energies shows that the square planar D_4h structure is more stable than the bidentate C_2v structure. The computed nucleus-independent chemical shifts (NICS) on the most stable D_4h structure show that the square planar La^2-_4 ring exhibits higher degree of aromaticity. The detailed MOs analysis further reveals that the square planar La^2-_4 ring possesses four independent delocalized bonding systems, each has two electrons satisfying the 4n + 2 electron counting rule of aromaticity, suggesting that these species have four-fold aromaticity.